The Ostrich in the Rock Art of Oman - El-Mahi, Ali Tigani (أدوماتو, 2001)
Keywords: Archéologie -- Oman

Did the Ancient Mesopotamian Royal Stone Originate in Oman ? - Yule, Paul A. (أدوماتو, 2001)
Keywords: Archéologie -- Oman

مقابر منطقة سمد الشان ، مادة علمية لدراسة التاريخ الحضاري في سلطنة عمان - Yule, Paul A. (أدوماتو, 2001)
Keywords: Archéologie -- Oman

The construction phases of Khor Rori's monumental gate - Avanzini, Alessandra; Orazi, Roberto (Arabian Archaeology and Epigraphy, 2001)
Keywords: Archéologie -- Oman

المستظهرون لكتاب الله العزيز بالقرارة (الحياة, 2001)
Keywords: Coran -- apprentissage

رسائل جماعية (الحياة, 2001)

من حصاد المطابع (الحياة, 2001)

الفكر الإسلامي: التوحد في التنزيل والتعدد في التأويل - أبو صالح, أمان (الحياة, 2001)

رسائل النبي (ص) إلى أهل عمان, دراسة تحليلية - الدروبي, محمد (الحياة, 2001)

من أسرار التنحيم في القرآن الكريم - الشيخ بالحاج, بكير بن محمد (الحياة, 2001)

بريد الحياة: الرسالة الأولى - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2001)

صورة الإباضية في العصر الرقمي - بابا عمي, محمد بن موسى (الحياة, 2001)

الوحدة الإسلامية كمقصد من مقاصد التشريع - بابكر, عبد الرحمن بن صالح (الحياة, 2001)

عرض مشكلة الديون في ظل الظاهرة التضخمية - بابكر, عبد الرحمن بن صالح (الحياة, 2001)

قصيدة: العالم الإسلامي اليوم - باجو, صالح بن إبراهيم (الحياة, 2001)
Keywords: Poésie -- Mzab

صلة الإجتهاد بالفكر العقدي والسياسي عند الإباضية - باجو, مصطفى بن صالح (الحياة, 2001)
Keywords: Ijtihad

مشكلة البيئة من منظور إسلامي - باجو, مصطفى بن صالح (الحياة, 2001)

مشوهات الإباضية نظرة من الداخل والخارج - بحاز, إبراهيم بن بكير (الحياة, 2001)

تقرير: معجم مصطلحات الإباضية - بن دريسو, مصطفى بن محمد (الحياة, 2001)

ملاحظات حول كتاب اللواح الخروصي - بوحجام, محمد بن قاسم ناصر (الحياة, 2001)

قراءة إقتصادية في صحف الشيخ أبي اليقظان - حمدي, محمد بن صالح (الحياة, 2001)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Journalisme -- Mzab

أفلا ينظرون إلى الإبل كيف خلقت؟ - حمدي عيسى, إبراهيم بن محمد (الحياة, 2001)

بريد الحياة: الرسالة الثانية - سوكحال, نور الدين (الحياة, 2001)

وثيقة الحياة: رسالة تاريخية من ليبيا - فخار, حمو بن عمر (الحياة, 2001)

قراءة جديدة في الفتاوى الإقتصادية للشيخ البكري - ناصر, سليمان بن الناصر (الحياة, 2001)
Keywords: Fatwas -- Mzab -- 20e siècle

الإفتتاحية - ناصر, محمد صالح (الحياة, 2001)

الخليل مربيا - ناصر, محمد صالح (الحياة, 2001)

من أعلام الفكر في الجزائر أبو يعقوب يوسف الوارجلاني - باجو, مصطفى بن صالح (مجلة جامعة الأمير عبد القادر للعلوم الإسلامية, 2001)
Keywords: Biographies -- Ouargla

الاجتهاد المقاصدي وتطبيقاته عند الإباضية - باجو, مصطفى بن صالح (مجلة جامعة الأمير عبد القادر للعلوم الإسلامية, 2001)
Keywords: Ijtihad

Review of Oman: Political Development in a Changing World - Deeb, Mary-Jane (The American Political Science Review, 2001)
Keywords: Recension

Review of Oman under Qaboos: From Coup to Constitution, 1970-1996, W. Lynn Rigsbee, II - Peterson, John E. (Middle East Journal, 2001)
Keywords: Recension

Review of Mehri Texts from Oman (Based on Field Materials of T. M. Johnstone) - Kaye, Alan S. (Journal of the American Oriental Society, 2001)
Keywords: Recension

مراكز المخطوطات في الجنوب الجزائري : إقليم توات نموذجاً - عوفي, عبد الكريم (آفاق الثقافة والتراث, 2001)
Keywords: Bibliothèques -- Mzab

Sultanat d'Oman : les femmes dessinent l'avenir du pays - Ley, Anne-Marie (Femmes suisses et le Mouvement féministe, 2001)

Les stratégies de reclassement des élites arabes et indiennes à Dar-es-Salaam durant la colonisation allemande (1891-1914) - Raimbault, Franck (Hypotheses, 2001)
Keywords: Relations -- Zanzibar -- Allemagne

An analysis of an Omani house in Stone Town, Zanzibar - Steyn, Gerald; Holm, Dieter (South African Journal of Art History, 2001)
Keywords: Architecture -- Zanzibar

الأحوال الاجتماعية لإقليم ظفار في العصر الإسلامي الوسيط - الدرويش, جاسم ياسين محمد; عبد الله, عاتكة حبيب (مجمة أبحاث البصرة, 2001)
Keywords: Dhofar

The Hasat Bani Salt in the al-Zahirah Province of the Sultanate of Oman - Yule, Paul A. (2001)
The Hasat Bani Salt is South-eastern Arabia's largest and most important rock art monument. Often referred to as Coleman's Rock, it is named after the geologist who, by word of mouth, made it known in expatriate circles in the 1980s. An improvement of its documentation allows a better idea regarding its dating and meaning.
Keywords: Géologie -- Oman

قرى واسماء مواضع في إقليم وارجلان من خلال ثلالث مصادر تاريخية - بوراس, يحيى بن عيسى (حوليات المتحف الوطني للآثار, 2001)

Aperçu succinct sur le fortin du site de Lalla Thala à Djerba (Tunisie) - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2001)
Keywords: Antiquité; Archéologie -- Djerba

Libyan studies on Italian colonialism: bibliographical and historiographical considerations - Venuta, Pierluigi (Journal of Libyan Studies, 2001)
Keywords: Bibliographie -- Libye

The senses of water in an Omani town - Limbert, Mandana E. (Social Text, 2001)

Trading through Islam: the interconnections of Sijilmasa, Ghana and the Almoravid movement - Miller, James Andrew (The Journal of North African Studies, 2001)
Keywords: Commerce transsaharien

Review: Mehri Texts from Oman: Based on the Field Materials of T. M. Johnstone, by Harry Stroomer. (Semitica Viva, Bd. 22) 303 pages, map, bibliography, footnotes, transcription table. Wiesbaden, Germany: Harrassowitz Verlag, 1999. DM168.00 (Paper) isbn 3-447-04215-X - Cross, Carmen (Middle East Studies Association Bulletin, 2001)
Keywords: Recension

The traditional pastoral groups of Dhofar, Oman: a parallel for ancient cultural ecology - ElMahi, Ali Tigani (Proceedings of the Seminar for Arabian Studies, 2001)
Keywords: Dhofar

‏صلة الاجتهاد بالفكر العقدي والسياسي عند الإباضية - باجو, مصطفى بن صالح (الحياة, 2001)
Keywords: Foi -- Ibadisme; Ijtihad

Observations on the archaeology and ethnohistory of rural estates of the 17th through early 20th centuries in Oman - Mershen, Birgit (Proceedings of the Seminar for Arabian Studies, 2001)
A description of the Ṣanʿa estate in the Wādī Banī Kharūṣ, now in the possession of Saʿūd, son of Sul. b. Ḥimyar al-Nabhānī. The latter, who once was paramount chief of the Banī Riyām, died in 1998, a few months after his return from exile.
Keywords: Archéologie -- Oman

Madkhal ilà Dirāsat Mashāghil al-ʿUlamā’ al-ʿUmāniyyīn - Azri, Khalid al- (نزوى: مجلة فصلية ثقافية, 2001)

Shuʿarā’ ʿUmān fī ‘l-Jāhiliyya wa-Ṣadr al-Islām - Sāmarrā’ī, Muḥammad Rajab al- (نزوى: مجلة فصلية ثقافية, 2001)
Keywords: Poésie -- Oman

Giolitti e San Giuliano di fronte alla questione della chiusura dell’impresa di Libia: annessione o protettorato? - Ferraioli, Gian Paolo (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2001)
La décision prise par le gouvernement italien, en octobre 1911, de ne pas donner le status de protectorat à la Libye constitua une des principales causes de la transformation de la guerre italo-turque en une guérilla longue et tragique entre les Arabes de Libye et les Italiens. En effet, le choix de Giolitti d'annexer directement la Libye au Royaume d'Italie poussa les Arabes à se joindre aux Turcs pour combattre contre le commun ennemi "chrétien". Pourquoi donc l'Italie rejecta-t-elle la formule du protectorat, si cette formule pouvait prévenir un tel danger? Cet article cherche à répondre à cette question, en analysant surtout la politique clairvoyante du ministre des Affaires étrangères du quatrième gouvernement Giolitti, le marquis Antonino di San Giuliano, qui fut réellement sur le point de mettre fin à la question de Libye avec un protectorat.
Keywords: Invasion italienne -- Libye

Tombs and their inscriptions from Nizwā and al-Ḥaymalī, Sultanate of Oman - Ibrahim, Moawiyah (Proceedings of the Seminar for Arabian Studies, 2001)
Keywords: Archéologie -- Oman

Religious discourse in the poetry of Abū Muslim al-Bahlānī - Maḥrūqī, Muḥammad al- (Journal of African Cultural Studies, 2001)
This article presents themes and techniques of the religious discourse of Abū Muslim al-Bahlānī. Al-Bahlānī was an Omani poet, born in Oman in 1860 who spent most of his life in Zanzibar where he died in 1920. His poetry is a good example of a strong link between art and politics. While the themes are centred around criticizing society and aiming to instigate revolution against people who do not follow Islamic laws, the techniques create harmony in the structure of this discourse. The author argues that this poetry is based on Ibāḍī sulūk, which itself can be considered as an extension of the Kharijite trend. Although, sulūk is linked with zuhd as a way of giving less value to this life, sulūk has some other implications which do not exist with zuhd. Hence, sulūk is not only a way of worshipping God, it is also a set of ideas which aim to change society and establish an Ibāḍī imamate. This attitude can be found with some sulūk leaders such as Jā'id al-Kharūṣī and Sa'īd al-Khalīlī.
Keywords: Poésie -- Oman

La réaction kharidjite et la naissance des royaumes indépendants du Maghreb (IIe-IIIe H./VIIe-IXe J.C.) - Chaouech, Salaheddin (Revue de la Faculté des Lettres de Tetouan, 2001)
Keywords: Kharijisme

The Anglo-Sanusi war (1915-1916) - Bernini, Simone (The Maghreb Review, 2001)
Keywords: Invasion italienne -- Libye

Review : Cook, Michael: (2000) Commanding right and forbidding wrong in Islamic thought. Cambridge: Cambridge University Press, 2000, (xvii, 702 pp.; 23x15 cm.). ISBN 0521661749. - Sajjad, Rizvi (Transcendent Philosophy, 2001)
Keywords: Recension

The Arab and Swahili culture in historical perspective. Some important links in “The history of the Mazrūʿīs in East Africa” by Shaykh al-Amīn b. ʿAlī al-Mazrūʿī - Soghayroun, Ibrahim (Sudanic Africa, 2001)
This paper presents Shaykh al-Amīn’s history of the Mazrūʿīs -an Omani tribe which was brought to Mombasa in about 1698- and evaluates its intellectual legacy to East Africa. Although the manuscript concentrates on the history of the Mazrūʿīs in East Africa, it comprises considerable material pertaining to other groups that played an important role in the history of the area. The Mazrūʿī history describes the interal factional struggles in Oman and its impact on East African Arab and Swahili communities. It also sheds light on the Portuguese and their policy during the period of their domination of the East African coast.
Keywords: Zanzibar

Al-Fueda near Amla, Sultanate of Oman - Bank, Charlotte; Yule, Paul A. (Proceedings of the Seminar for Arabian Studies, 2001)
Keywords: Archéologie -- Oman

Race and Class in the Politics of Zanzibar - Sheriff, Abdul Mohamed Hussein (Africa Spectrum, 2001)
Keywords: Zanzibar

Kheireddine Pacha et son projet de musée archéologique à Tunis - Jaïdi, Houcine (Pallas, 2001)
Keywords: Musée -- Tunis

Werner Vycichl 1909-1999 in memoriam - Lucchesi, Enzo (Wiener Zeitschrift für die Kunde des Morgenlandes, 2001)
Keywords: Biographies -- Suisse

Oman under Qabus: From Coup to Constitution, 1970-1996 by Calvin Allen, Jr.; W. Lynn Rigsbee, II - Rabi, Uzi (Middle Eastern Studies, 2001)
Keywords: Recension; Vie politique -- Oman -- 1970-2020

القيم الانسانية في شعر الخوارج - نصير, أمل طه (مجلة المجمع العلمى, 2001)
Keywords: Poésie kharijite

1560 Cerbe Deniz Zaferi Ve Cerbe Kalesinin Fethi - Önalp, Ertuğrul (Ankara Üniversitesi Osmanlı Tarihi Araştırma ve Uygulama Merkezi Dergisi, 2001)
[The sea victory of Jerba and the capture of the castle of Jerba].
Keywords: Invasions chrétiennes -- Djerba -- 1560

Island of silences (Sight and Sound, 2001)
Keywords: Littérature -- Djerba

The homecoming - Halberstadt, Ilona (Sight and Sound, 2001)
Keywords: Recension

Jeux de parcours du monde arabo-musulman (Afrique du Nord et Proche-Orient) - Depaulis, Thierry (International Journal for the Study of Board Games, 2001)
Keywords: Jeux -- Djerba

Tunisie: La mémoire des Juifs de Djerba. Yaacov Bchiri - Weissenberg, Luc (Cahiers de musiques traditionnelles, 2001)
Keywords: Judaïsme -- Djerba; Recension

At the Origins of the Settlement of Zanzibar: The Cave of Machaga - Wafula, G. K. (Tarehi, 2001)
Keywords: Archéologie -- Zanzibar

Le voyage mystique - Koraïchi, Rachid (Etudes littéraires, 2001)
Keywords: Artisanat -- Djerba

Droits et place de la femme tunisienne à travers le film « la saison des hommes » - Gabsi, Abdallah (Saout el Jalia, 2001)
Keywords: Moeurs et coutumes -- Djerba

Le Houch Djerbien : Pour une meilleure connaissance de l’architecture domestique traditionnelle de Djerba - Yacoub, Hichem (Cahier des Arts et Traditions populaires, 2001)
Keywords: Architecture -- Djerba

Il Berbero di Jerba: Secondo Preliminare - Brugnatelli, Vermondo (Incontri Linguistici, 2001)
Keywords: Linguistique

Kisse Raḥamim — Talmud Exegesis in Djerba by Rabbi Raḥamim Ḥury - Ahrend, Aaron (Shenaton ha-Mishpat ha-Ivri: Annual of the Institute for Research in Jewish Law, 2001)
Keywords: Judaïsme -- Djerba

Optimisation de la consommation énergetique dans la station de dessalement de Zarzis (12,000 m3/j) - Fethi, Kamel (Desalination, 2001)
Keywords: Energies renouvelables -- Djerba

Analysis of the essential oil of Artemisia campestris L. - Akrout, Ahmed; Chemli, Rachid; Chreïf, Imed; Hammami, Mohamed (Flavour and Fragrance Journal, 2001)
The composition of the essential oil obtained by hydrodistillation from the aerial parts of several populations of Artemisia campestris L. (Asteraceae), collected from four areas of south-eastern of Tunisia (Bengardane, Benikhdache, Jerba and Tataouine), was analysed by GC–MS. Thirteen to fifteen components were identified in each sample, representing more than 95% of the total oil. All samples were dominated by the presence of β-pinene (24.2–27.9%), p-cymene (17.4–22.3%) and α-pinene (4.1–11.0%), representing more than 45% of the total oil. The distribution of other components in the different extracts was qualitatively and quantitatively irregular. The variability of the composition can be attributed to the climatic and geographical conditions among areas
Keywords: Artemisia campestris L. -- Djerba; Botanique -- Djerba

Note sur l’utilisation du sel ou de l’eau de mer chez les potiers de Tunisie - Mrabet, Abdellatif (Cahiers des Arts et Traditions Populaires, 2001)
Keywords: Artisanat -- Djerba

Le pélerinage tunisien de Sarcelles: De la tradition à l’hédonisme contemporain - Podselver, Laurence (Socio-anthropologie, 2001)
Keywords: Judaïsme -- Djerba

Villas, wine and kilns: the landscape of Jerba in the late Hellenistic period - Fentress, Elizabeth (Journal of Roman Archaeology, 2001)
The island of Jerba emerges unobtrusively from its shallow waters. The landscape is flat, the vegetation varies from scrubland to sparse palms to large olive trees whose ample root-stocks suggest several centuries of life. The olive groves are ploughed to allow every possible drop of water to reach the roots. Dry farming of cereals is more or less pointless although, when rain is plentiful, barley will be thinly sown on land that is otherwise uncultivated. In this driest of Mediterranean zones, plentiful rain is barely more than the few showers which the 200-mm isohyet would suggest. In the interior of the island a few estates maintain irrigated cultivation, the luxuriant results of which recall Pliny's description of the oasis of Tacape; palms shelter fruit trees, which shelter pomegranates, which in turn shelter little vegetable plots. Wells provide water for these systems, the water trickling into the gardens through tiny channels (sāqiya). Today the water is pumped, but in the past each bucket had to be laboriously raised by mules or camels; their ramps form a distinctive component of the systems. High walls of mud (ṭābiya) enclose the irrigated gardens. However, in spite of the technological improvements, these gardens are less plentiful than in the past and, as the water table falls, it is more common to find an abandoned well than one in use.
Keywords: Antiquité; Archéologie -- Djerba